2019
DOI: 10.1101/2019.12.27.889469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CSF1R inhibition by a small molecule inhibitor affects hematopoiesis and the function of macrophages

Abstract: Colony-stimulating factor 1 receptor (CSF1R) inhibition has been proposed to specifically deplete microglia without affecting peripheral immune cells. Here, we show that CSF1R inhibition by PLX5622 causes changes in the myeloid and lymphoid compartments and longterm functional impairment of bone marrow-derived macrophages by suppressing their IL-1β expression, phagocytosis, and M1, but not M2 phenotype. Thus, CSF1R inhibition with small

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…These "control" mice we refer to as "microglia sufficient" mice. Interestingly, although PLX5622 was recently shown to reduce lymphoid and myeloid cell numbers with a 3-week treatment (Lei et al, 2020;Spiteri et al, 2022), we speculated that the prolonged treatment regimen could have yielded this result. Therefore, we used PLX at a high concentration (660 mg/kg) to facilitate rapid microglial cell elimination.…”
Section: Pharmacological Microglial Elimination and Repopulationmentioning
confidence: 89%
“…These "control" mice we refer to as "microglia sufficient" mice. Interestingly, although PLX5622 was recently shown to reduce lymphoid and myeloid cell numbers with a 3-week treatment (Lei et al, 2020;Spiteri et al, 2022), we speculated that the prolonged treatment regimen could have yielded this result. Therefore, we used PLX at a high concentration (660 mg/kg) to facilitate rapid microglial cell elimination.…”
Section: Pharmacological Microglial Elimination and Repopulationmentioning
confidence: 89%
“…Although CSF1R inhibitors primarily deplete microglia, they can target other peripheral immune cells. Monocyte and macrophage subsets express CSF1R and can be vulnerable to depletion (Lei et al, 2020). Few studies have investigated the peripheral effects of CSF1R inhibition after TBI.…”
Section: Effect Of Csf1r Inhibition On Peripheral Immune Cellsmentioning
confidence: 99%
“…As discussed, the use of CSF1R inhibitors is an emerging technique with demonstrated efficacy in the ablation of microglia in the CNS (Elmore et al, 2014;Fujiwara et al, 2021). The CSF1R inhibitors, such as PLX3397 and PLX5622, are CNS-permeable and selectively inhibit tyrosine kinase receptors on macrophages and microglia, although the specificity of these inhibitors varies depending on the specific compound used (Green et al, 2020;Hupp and Iliev, 2020), with PLX5622 recently shown to exert effects on peripheral bone marrow and tissue-resident macrophages (Lei et al, 2020). CSF1R inhibitors are orally bioavailable, but their routes of administration can also include intravenous or subcutaneous injection (Hupp and Iliev, 2020).…”
Section: Pharmacological Depletion Of Microgliamentioning
confidence: 99%